Investigating the role of refuges and drift on the resilience of macroinvertebrate communities to drying conditions: An experiment in artificial streams. (1st June 2018) - Doretto, A.; Piano, E.; Falasco, E.; Fenoglio, S.; Bruno, M.C.; Bona, F.
Abstract: Flow intermittence occurs in an increasing number of streams, due to climate change, local land‐use alteration and water abstraction. In particular, droughts represent a new element in Alpine river regimes, and their ecological consequences are poorly explored. We here used artificial streams to investigate the resilience of macroinvertebrates to drought in Alpine streams based on the presence of pools (i.e., refuges) and drift (i.e., recolonization). Three flumes were selected: 1 with permanent flowing water (Control), whereas the other 2 (Drift+Pools, Only Drift) were subjected to 2 consecutive drought‐rewetting phases. Moreover, to better monitor the recolonization pattern by drift, quantitative samples of drifting taxa were collected using an additional flume (Incoming Drift). The effects of droughts on benthic invertebrate communities and their recovery were assessed in terms of composition, structure, diversity, and stability. Droughts dramatically reduced the taxa richness, especially with regard to the most sensitive and specialized macroinvertebrates, such as Ephemeroptera, Plecoptera, and Trichoptera taxa. Macroinvertebrate assemblages of the flumes that experienced drying phases were dominated by few generalist taxa and showed a higher degree of dissimilarity. Overall, no significant differences were observed in relation to the presence of pools, suggesting a limited role of this habitat in the recovery process. This finding suggests that in shallow and fast‐flowing Alpine lotic ecosystems the drift rather than pool availability represents the main driver of the macroinvertebrate resilience to droughts and provides insights into factors that can facilitate the recovery of aquatic communities after droughts.